2023
DOI: 10.3390/antiox12010139
|View full text |Cite
|
Sign up to set email alerts
|

Seleno-Analogs of Scaffolds Resembling Natural Products a Novel Warhead toward Dual Compounds

Abstract: Nowadays, oxidative cell damage is one of the common features of cancer and Alzheimer’s disease (AD), and Se-containing molecules, such as ebselen, which has demonstrated strong antioxidant activity, have demonstrated well-established preventive effects against both diseases. In this study, a total of 39 Se-derivatives were synthesized, purified, and spectroscopically characterized by NMR. Antioxidant ability was tested using the DPPH assay, while antiproliferative activity was screened in breast, lung, prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…The synthesis procedure and the characterisation of the compounds were described in our previous study. 30 Briefly, hydrogen sodium selenide (NaHSe) was formed by the reduction of elemental Se with NaBH 4 in water. Then, the corresponding acid chloride was added to the reaction mixture to form the corresponding sodium selenoate by a nucleophilic acyl substitution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis procedure and the characterisation of the compounds were described in our previous study. 30 Briefly, hydrogen sodium selenide (NaHSe) was formed by the reduction of elemental Se with NaBH 4 in water. Then, the corresponding acid chloride was added to the reaction mixture to form the corresponding sodium selenoate by a nucleophilic acyl substitution.…”
Section: Resultsmentioning
confidence: 99%
“…Reagents and conditions: (i) H 2 O, 20 min, and room temperature; (ii) THF/H 2 O, 60 min, and room temperature; (iii) ClCOCOCl, CH 2 Cl 2 , 12 h, and room temperature; (iv) BrCH 2 CH = CH 2 or BrCH 2 C≡CH, THF/H 2 O, 90 min, and room temperature. 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis tests were conducted using the Muse Annexin V/7‐AAD and Caspase 3/7‐7‐AAD kit from EMD Millipore, Darmstadt, Germany, following the provided protocol as described in Astrain‐Redin et al. (2023). The cells were initially seeded in a 6‐well plate at a density of 1 × 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, a multitude of compelling studies have reported that they can act only for limited periods and present a risk of harmful side effects. To overcome these drawbacks, researchers are eager to find and develop innovative candidates to combat this disorder. In this line, burgeoning evidence revealed that a wide range of selenocompounds has great effectiveness in AD. …”
Section: Selenized Small Molecule Drugsmentioning
confidence: 99%